REVIEW OF THE INTERNATIONAL MONETARY SYSTEM AND THE THEORY OF MONETARY SYSTEMS by Pascal Salin - Van Den Hauwe, PH.D., Ludwig (REVISTA PROCESOS DE MERCADO, 2022)
Except for some minor issues, previous reviews of the book (Dorobat 2017; Cutsinger 2017/18) have been overwhelmingly positive and for good reason. The book under review is the fruit of several decades of economic thinking, professional research, writing and teaching of its author Emeritus Prof. Pascal Salin of the Université Paris-Dauphine and past president of the Mont Pèlerin Society.